2016
DOI: 10.1016/j.rpto.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Employment testing online, offline, and over the phone: Implications for e-assessment

Abstract: a b s t r a c tThis research investigated faking across test administration modes in an employment testing scenario. For the first time, phone administration was included. Participants (N = 91) were randomly allocated to testing mode (telephone, Internet, or pen-and-paper). Participants completed a personality measure under standard instructions and then under instructions to fake as an ideal police applicant. No significant difference in any faked personality domains as a function of administration mode was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…For example, Murphy and Dzieweczynski (2005) posited that the theories linking personality constructs and job performance were often vague and unconvincing, that little was known about how to match personality dimensions and occupations, and that some of the most valid personality-related measures (e.g., integrity tests) included poorly defined constructs. On the other hand, researchers suggested that the validity of personality measures was small and that the measures based on self-reports can be faked, independently of the administration mode (Grieve & Hayes, 2016;Morgeson et al, 2007aMorgeson et al, , 2007bSalgado, 2016).…”
mentioning
confidence: 99%
“…For example, Murphy and Dzieweczynski (2005) posited that the theories linking personality constructs and job performance were often vague and unconvincing, that little was known about how to match personality dimensions and occupations, and that some of the most valid personality-related measures (e.g., integrity tests) included poorly defined constructs. On the other hand, researchers suggested that the validity of personality measures was small and that the measures based on self-reports can be faked, independently of the administration mode (Grieve & Hayes, 2016;Morgeson et al, 2007aMorgeson et al, , 2007bSalgado, 2016).…”
mentioning
confidence: 99%
“…Despite the empirical evidence of the validity of the FFM, several researchers have criticized personality variables on the basis that they can be affected by faking when the individual is motivated to do it, for instance, in personnel selection processes (Grieve & Hayes, 2016;Morgeson et al, 2007;Salgado, 2016).…”
mentioning
confidence: 99%
“…With regard to future research, the significant growth in the use of new information technologies (IT) in the selection and assessment processes (e.g., e-recruitment, phone-based interviews, online interviews) suggests that new studies should be conducted to verify the way in which the findings of the present research can be transported to new assessment methods (Aguado, Rico, Rubio, & Fernández, 2016;Bruk-Lee et al, 2016;García-Izquierdo, Ramos-Villagrasa, & Castaño, 2015;Schinkel, van Vianen, & Ryan, 2016). This is especially relevant in the case of the interview, given that more and more companies are conducting online interviews, in which the interviewer and the interviewee communicate only through a computer and in which there is no real interaction between the interviewer and the interviewee (Grieve & Hayes, 2016;Silvester & Anderson, 2003).…”
Section: Implications For Practice and Future Researchmentioning
confidence: 82%